Phase-transfer catalyzed enantioselective alpha-alkylation of alpha-acyloxymalonates: construction of chiral alpha-hydroxy quaternary stereogenic centers - Ha, Min Woo; Choi, Sujee; Kim, Seek; Lee, Jun Young; Lee, Jae Kyun; Lee, Jeeyeon; Hong, Suckchang; Park, Hyeung-geun (ROYAL SOC CHEMISTRY, 2016)
The enantioselective synthesis of alpha-acyloxy-alpha-alkylmalonates was developed as an efficient method for producing chiral alpha-tertiary alcohols, which are potentially valuable intermediates in the synthesis of natural products and pharmaceuticals. The efficient enantioselective alpha-alkylation of diphenylmethyl tert-butyl alpha-acyloxymalonates was accomplished via phase-transfer catalysis in the presence of (S, S)-3,4,5-trifluorophenyl-NAS bromide to afford the corresponding alpha-acyloxy-alpha-alkylmalonates at high chemical (up to 99%) and optical (up to 93% ee) yields, which could be readily converted to versatile chiral intermediates with a chiral alpha-tertiary alcohol group.
Keywords: PIG-LIVER ESTERASE; BETA-KETO-ESTERS; ASYMMETRIC-SYNTHESIS; AMINO-ACIDS; STEREOSELECTIVE-SYNTHESIS; ORGANIC-SYNTHESIS; ATOM-TRANSFER; AMINOXYLATION; (R)-BICALUTAMIDE; KETOESTERS